(untitled) - Miron, Dougas B. (Amsterdam, 2006)
This book will provide you with the knowlegde to successfully design physically small antennas for a wide range of mobile and portable applications
Keywords: Radio,Radio; Antennas,Design and construction.,Anten,Thiết kế